Synchronised measurement devices for power systems with high penetration of inverter‐based renewable power generators. Issue 1 (20th September 2018) - Liu, Hao; Li, Jue; Li, Jiaxian; Tian, Jiannan; Bi, Tianshu; Martin, Kenneth E.; Yang, Qixun
Abstract : The deployment of more and more power electronic devices results in the sub‐synchronous oscillation caused by sub/super‐synchronous harmonics associated with inverter‐based renewable power generators (IRPGs). New measurement devices are needed to monitor the operation states of renewable power generator (RPG) areas. In this study, a synchronised measurement device for power systems with high penetration of IRPGs (SMD‐R) is proposed and developed. Unlike traditional synchronised measurement devices, an SMD‐R is able to perform real‐time inter‐harmonics and fundamental phasor estimation that are reported by different data frames in different rates by being installed inside a wind turbine or an integration station of RPG. The integration of SMD‐R and the message format for inter‐harmonics are outlined. A spectrum line curve fitting based algorithm is proposed to estimate inter‐harmonics via a short data window. To track the dynamic process of RPG areas fast and precisely, an adaptive fundamental phasor algorithm based on phasor parameter behaviours identification is developed. The proposed SMD‐R is implemented in a CompactRIO of National Instruments. Experiment results verify the accuracy and effectiveness of the proposed device.